The Effect of Problem Posing Learning on Mathematical Communication Ability of Fourth Grade Students of State Elementary School 101390 Batang Pane 1 Academic Year 2022/2023 - Adinda Sabila Rahma (Journal of General Education Science, 2022)
The purpose of this research is toto know the mathematical communication skills before and after using the Problem Posing learning model for the fourth grade students of SDN 101390 Batang Pane 1 in the 2022/2023 academic year and to determine the effect of Problem Posing Learning on the Mathematical Communication Skills of the fourth graders at SDN 101390 Batang Pane 1 in the 2022/2023 academic year. This study uses a quantitative approach. The results showed that the students' mathematical communication skills before using the Problem Posing learning model could be seen from the students' activities in the teaching and learning process during the learning process which was very low where 3 students had met the KKM score and 31 students had not met the KKM score. with an average value of 66.78.